The role of classroom activities in developing dialogue skills among pupils from the point of view of teachers of the first cycle in schools in Hama (Journal of Hama University, 2022)
This research aims to find out the degree of approval of teachers in the first stage of the basic education stage about the role played by activities within the classes in the development of dialogue skills as a whole and every skill at their pupils, The researcher selected a random sample of the teachers of the first episode, The number of male and female teachers reached 93, By a percentage that exceeds (11%) the size of the original community to be studied, The researcher adopted analytical descriptive approach, The questionnaire was used as a tool to collect information and data, It consisted of five axes. Each axis dealt with the role of classroom activity in developing one of the five dialogue skills (Communication skill, listening, verbal expression, critical thinking and conflict resolution skill), The process of analyzing the results resulted in the approval of the sample members that the classroom activities develop dialogue skills to a moderate degree, The arithmetic mean of the degree of their agreement was (2.80) and a standard deviation (0.92), As for the degree of their agreement about its role in developing sub-dialogue skills (each separately), it ranged between low and high in general, The communication skill was ranked first with a high degree of approval, The skill of listening ranked second, with an average degree of approval, The third place was for the skill of oral expression, and a moderate degree of agreement, The fourth rank was for the skill of critical thinking, with a low degree of agreement, The skill of resolving conflicts ranked fifth and last, and a low degree of agreement as well, The results also showed that there was a statistically significant difference (at a significance level of 5%) between the average responses of the sample individuals in developing students' dialogue skills according to the gender variable (in favor of females), and the scientific qualification variable (in favor of the class teacher), And there is no difference between them according to the experience variable. The study concluded with several proposals.